The Arabic Linguistic Landscape of Islamic Universities: Patterns, Strategies, and Pedagogical Practices in West Sumatra - Musalwa; Rahmat Satria Dinata; Syafrimen Syafril; Ahmad Basyori; Vanadya Amelia; Putri Amelia; Salah Benrabah (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2025)
This study investigates the Arabic linguistic landscape in Islamic universities across West Sumatra by examining its writing patterns, strategies, and related pedagogical practices. Employing a mixed-methods approach with an exploratory sequential design grounded in Creswell’s framework, the research found that bottom-up patterns dominate text production, while the most frequently used strategy is Fragmentary Multilingual Writing. This strategy involves combining Arabic with other languages without complete translation, reflecting a natural yet underutilized linguistic environment in structured pedagogical contexts. Most respondents acknowledged that the presence of Arabic texts in campus public spaces contributes positively to the development of a rich linguistic environment (bi’ah lughawiyah) and can serve as an effective medium for Arabic language instruction. Practically, the findings provide strategic direction for institutions to manage the linguistic landscape as an authentic learning tool and a foundation for institutional language policy. Theoretically, the study broadens the scope of Arabic as a Foreign Language (AFL) research by highlighting the role of multilingual signage within formal Islamic university contexts as part of a dynamic and integrated learning ecosystem.